BEACCTIVE as educational leadership model to create partnerships with business and industry - Danny Meirawan; Heni Mulyani; Kholifatul Husna Asri (LPMPP Universitas Negeri Yogyakarta, 2022)
This study aims to analyze how the partnership of vocational schools with business and industry through the education leadership model. The research used a quantitative approach with an explanatory survey method. Proportionated stratified random sampling technique was used in this research. A total of 1.630 respondents consists of principals, the head of the expertise program, the deputy principal for curriculum, the deputy principal for public relations, and teachers who participated in this research. The instrument used is a questionnaire. The data analysis used was multiple regression. The results showed that the BEACCTIVE model could be a determining factor for the success of establishing a partnership. The reason is that the partnerships were developed through the formulation of plans, human resource management, decision making, and the ability of school principals to attract business and industry. The school's partnership with business and industry has a good fit and improves through programs centred on students' skills and expertise aligned with standards of business and industry, the business and industry that actively support the educational practices at schools and the absorption of graduates in various industrial sectors.